Recommendations on practice of conditioned pain modulation (CPM) testing - Yarnitsky, David; Treede, Rolf-Detlef (European journal of pain, 2015)
Protocols for testing conditioned pain modulation (CPM) vary between different labs/clinics. In order to promote research and clinical application of this tool, we summarize the recommendations of interested researchers consensus meeting regarding the practice of CPM and report of its results.
Gesehen am 08.02.2018